Deletion of the Protein Kinase A/Protein Kinase G Target SMTNL1 Promotes an Exercise-adapted Phenotype in Vascular Smooth Muscle - Wooldridge, Anne A.; Fortner, Christopher N.; Lontay, Beata; Akimoto, Takayuki; Neppl, Ronald L.; Facemire, Carie; Datto, Michael B.; Kwon, Ashley; McCook, Everett; Li, Ping; Wang, Shiliang; Thresher, Randy J.; et al. (East Carolina University, 2008)
In vivo protein kinases A and G (PKA and PKG) coordinately phosphorylate a broad range of substrates to mediate their various physiological effects. The functions of many of these substrates have yet to be defined genetically. Herein we show a role for smoothelin-like protein 1 (SMTNL1), a novel in vivo target of PKG/PKA, in mediating vascular adaptations to exercise. Aortas from smtnl1-/- mice exhibited strikingly enhanced vasorelaxation before exercise, similar in extent to that achieved after endurance training of wild-type littermates. Additionally, con- tractile responses to alpha-adrenergic agonists were greatly attenuated. Immunological studies showed SMTNL1 is expressed in smooth muscle and type 2a striated muscle fibers. Consistent with a role in adaptations to exercise, smtnl1-/- mice also exhibited increased type 2a fibers before training and better performance after forced endurance training compared smtnl1+/+ mice. Furthermore, exercise was found to reduce expression of SMTNL1, particularly in female mice. In both muscle types, SMTNL1 is phosphorylated at Ser-301 in response to adrenergic signals. In vitro SMTNL1 suppresses myosin phosphatase activity through a substrate-directed effect, which is relieved by Ser- 301 phosphorylation. Our findings suggest roles for SMTNL1 in cGMP/cAMP-mediated adaptations to exercise through mechanisms involving direct modulation of contractile activity. Originally published Journal of Biological Chemistry, Vol. 283, No. 17, Apr 2008
Keywords: Exercise adapted phenotype; Protein kinases; Vascular smooth muscle